Decision to employ retired nurses to work in senior care businesses: A qualitative study - Wonpen Kaewpan; Kunwadee Rojpaisarnkit; Sulee Tongvichean; Lalita Kaewwilai; Thapanut Keawpan (Wiley, 2023)
Abstract Aims This paper aimed to explore the views of employers at senior care businesses concerning the employment of retired nurses in Thailand. Design A qualitative interview study was conducted. Methods Face‐to‐face and online semi‐structured interviews with 78 senior care business employers were conducted. Results Business employers had positive sentiments towards employing retired nurses to deliver care and supported them to remain in the profession. Business employers acknowledged that retired nurses have a high level of professional confidence with excellent knowledge and skills. Furthermore, retired nurses were often assigned to work in managerial roles. In addition, flexibility in terms of work hours, suitability of role and responsibilities, and reasonable compensation rates were important to nurses' decisions to remain in or return to the nursing profession. There is a need for the further development of recruitment, retention and reform policies to encourage retired nurses to continue or return to the nursing profession. Patient and Public Contributions We thank all participants for their valuable input throughout the study.